Symposium 2: Xploring txtuality & txtually transmitd dis-Ez: Exploring textuality & textually transmitted dis-ease - Haxell, Ailsa (Proceedings of the International Conference on Networked Learning, 2014)
In studying the sociology of translation, there is logic in attempting to stay as true to form as possible in reporting on studies, for what is known is that in the performance of reporting, further translations occur. Furthermore, additional and perhaps unnecessary distortions occur when the research is disseminated. Taking a performative turn, research dissemination attends to more than the aesthetic. In investigating how young people become positioned in their preference for texting, what is shown is positioning that trivializes, pathologizes and marginalizes. In only attending to a sanitized voice, one made to fit the academic audience, translated into the discourse of those situated in the mainstream, processes of colonization and oppression are perpetuated. In giving academic credence to particular voices and not others, conventions of academia support a dominant discourse: "to be taken seriously do not stay as you are". This paper therefore focuses on a particular aspect of research, the collateral damage of research dissemination that restricts and alters voice. To redress violence against such voices, a performative turn is taken. This paper explores textuality and textual dis-ease as a dialogically provocative texted performance. I present text language as non-trivial and non-pathological. In presenting this research my intention is not to provide a spectator’s view on some private world, nor to entertain, but to engage with you in a performance that runs interference on conventions that would marginalize and oppress. In doing so, a sociology of translation provokes understanding not only of things both technical and social, but also political; of practice realities involving those “othered” and perhaps better understanding of how we too may be “othering”.